Polybrominated Diphenyl Ethers, Polychlorinated Dibenzo-dioxins, -furans, and -biphenyls in Three Species of Antarctic Penguins - CORSOLINI, S.; BORGHESI, N.; SCHIAVONE, A.; FOCARDI, S. (Environmental Science and Pollution Research - International, 2006)
Background, Aims and Scope. Fish-eating seabirds are recognized to be at risk of accumulating toxic contaminants due to their high position in the trophic web and to their low ability to metabolize xenobiotic compounds. Penguins are widely distributed in Antarctica and represent an important fraction of the Antarctic biomass. They feed mainly on krill and, depending on krill availability, also on fish. It has been reported that predators may be a sink for volatile and toxic chemicals and this may pose a serious environmental problem. Polybrominated diphenyl ethers (PBDEs), polychlorinated dibenzo-dioxins (PCDDs), -furans (PCDFs), and -biphenyls (PCBs), including non-ortho congeners, hexachlorobenzene (HCB) and p,p'-DDE, were quantified in three species of Antarctic Pygoscelids in order to evaluate their accumulation patterns. The potential toxicity of twenty-two dioxin-like congeners was assessed and expressed as 2,3,7,8-tetra CDD equivalents (TEQs). Differences between males and females were investigated. Methods. Blood samples of the Adelie penguin Pygoscelis adeliae, Chinstrap penguin Pygoscelis antarctica and Gentoo penguin Pygoscelis papua were collected at Admiralty Bay, King George Is (62 degrees 10'39" S, 58 degrees 26'46" W) in February 2004. Halogenated hydrocarbons were identified and quantified using gas chromatography coupled with gas chromatography mass spectrometry analyses. Results are expressed on a wet weight basis. Results and Discussion. HCB, p,p'-DDE and Sigma PCBs were higher in Adelie penguins (6.7 +/- 6.1, 8.2 +/- 3.3 and 9.8 +/- 3.8 ng/g, respectively) than in Chinstrap and Gentoo penguins, both of which showed values in the same order of magnitude, but approximately 40% lower than Adelie penguins. Hexa-CBs ranged 35-45% of the residue. Low-chlorinated PCBs (nos. 70+76+95+56+60+101) accounted for 40-60% in the three species. PCB101 made up 15% of,the residue in Adelie penguins. PBDEs were 291 +/- 477, 107 +/- 104 and 116 +/- 108 pg/g in Adelie, Chinstrap and Gentoo penguins, ...